PENINGKATAN PEMAHAMAN SAINS BIOLOGI MELALUI PERMAINAN KARAMBOL - SUBHAN, SUBHAN (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
The aim of this study is to describe the process and results of learningthrough play carom that can improve scientific understanding of biologicalchildren in RA B1 Salsabila Jakarta Year 2015/2016. The subjects of this studywere 22 children. This research method is based on the Research Action ClassAction Research model Kemmis and Mc. Taggart which includes four stages:planning, action, observation, and reflection. This study consisted of two cycles,each cycle consisting of 8 times pertemuan.Teknik data analysis used in thisresearch is the analysis of qualitative and quantitative data. Analysis ofqualitative data by analyzing data from interviews during the study to the steps ofdata reduction, data display and data verification. Quantitative data analysis withdescriptive statistics to compare the results obtained from pre-intervention, thefirst cycle and the second cycle. The results of this study showed an increasedunderstanding of sains biologi children through play carom, evidenced by anaverage understanding of sains biologi score of 41.59 pre-intervention, thenincreased in the first cycle of the second cycle of 63.82 and 80.73.